UPAYA FOUR PAWS INTERNASIONAL DALAM PERLINDUNGAN KESEJAHTERAAN HEWAN DI JALUR GAZA, PALESTINA - Nadhifa, engku Lifia; Fuadi, Ahmad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
The Gaza Strip is a conflict zone that has long experienced blockades, political instability, and armed violence, leading to an ongoing humanitarian crisis. Not only humans but also animals have become victims of this situation, particularly those in zoos that are left neglected and lacking proper care. Amidst this turmoil, Four Paws International, a non-governmental organization focused on animal welfare, carried out a mission to rescue animals in Gaza during 2018–2019. This study employs a descriptive qualitative approach with a non-participatory observation method, using social movement theory and pluralism perspective in international relations as theoretical frameworks. Social movement theory provides an understanding of the processes of mobilization, solidarity, and the formation of global advocacy networks, while the pluralism perspective helps illustrate how non-state actors, such as Four Paws International, can influence international regimes that are typically dominated by states. The study also uses the Five Freedoms framework by the Farm Animal Welfare Council (FAWC) as a benchmark to assess animal welfare standards. The findings show that Four Paws International executed animal rescue efforts through evacuation and medical care methods. The organization successfully evacuated dozens of animals from three zoos in Gaza, all in critical conditions, to wildlife sanctuaries in Jordan and South Africa. With the documented process of evacuation and post-evacuation care conducted by the organization, Four Paws International's mission in Gaza can be categorized as successful. This success is reflected in the physical and mental recovery of the animals, who had previously been exposed to hazardous conditions, ensuring they received better protection after evacuation and demonstrating a significant contribution to animal welfare protection in conflict zones. Keywords: Four Paws International, Gaza, Animal Welfare, Social Movements, Pluralism, Conflict Zon.